Does voter turnout affect the votes for the incumbent government? - Martins, Rodrigo (2014)
This paper analyzes the effects of voter turnout on the vote shares received by the incumbent government. A system of simultaneous equations is estimated using a panel dataset of 278 Portuguese municipalities, for the period 1979–2005, covering 10 legislative elections. The results indicate that right-wing governments have lower vote shares when turnout is higher, while leftwing ones seem to be unaffected. There is also evidence of the responsibility hypothesis, that turnout is higher in closer elections, and that regional/local economic variables have non-linear effects on turnout implying that it is higher in good and bad times, but lower when the economy is neither too hot nor too cold.